A longitudinal study on possible correlates that might explain the onset and progression of musculoskeletal symptoms in school-aged children with Generalized Joint Hypermobility - Ituen, Oluwakemi Adebukola (Division of Physiotherapy, 2025)
Background: Generalized Joint Hypermobility (GJH) is an increased joint range of motion in multiple joints. Its prevalence in the general population is usually a function of age, gender, ethnicity and Beighton score cut-off score. GJH has been documented to be beneficial to sports and activities that require flexibility. Despite this advantage, it is assumed that joint laxity distorts joint biomechanics increasing their risk of injuries and pain. This has remained inconclusive in the literature because not all children with GJH develop musculoskeletal pain. In addition, previous studies have tested proprioception, balance and strength as possible underlying factors facilitating the onset of musculoskeletal symptoms in GJH. Yet, studies using different instruments and test positions have been inconclusive about the association. In addition, the psychosocial consequence of GJH is yet to be explored. Our study was aimed at following up on the same group of children, taking three assessments of proprioception, functional strength and dynamic balance over a period of two years and investigating how they may influence the development of musculoskeletal symptoms in school-aged children with GJH. The children's physical fitness, functional difficulties, physical activity levels and quality of life were also measured during the study period. Methods: A prospective longitudinal study design was used. We recruited 198 children aged 6-8 years at the beginning of the study. We classified them based on their joint mobility using the Beighton scoring system with goniometry. Strength, dynamic balance, physical fitness and proprioception were assessed using the Functional Strength Measurement, Y-Balance, Shuttle run test and Wedges test, respectively. The Child Activity Limitation Interview questionnaire version 21 (CALI-21) was used to document functional difficulties; the Physical Activity questionnaire was used to evaluate the children's physical activity level, while the children's quality of life was determined using the Pediatric Quality of Life questionnaire. The Wong-Baker FACES was used to determine the participants' pain level. Results: A total at 195 children entered the study and 69 were lost to follow-up due to relocation or change of school at the end of the study. Proprioception, strength and balance were not different between mobility groups at the end of the study. Physical activity levels between children with and without GJH were significantly different at the end of the study. The overall quality of life was not different between the mobility groups. Conclusion: We found a high prevalence of GJH (64.7%), and the inclusion of goniometry in the Beighton scoring system provided more specific information on joint hypermobility. None of the children with joint hypermobility developed HSD. The incidence of pain among children with GJH was so low that factors (proprioception, balance, or strength) mentioned in the literature could not be used to predict the onset of musculoskeletal symptoms in GJH. Contrary to previous findings in the literature, children with GJH in our study were not different in proprioception, dynamic balance, and functional strength compared to children with normal mobility. The outcome of this longitudinal study confirms that these factors (proprioception, dynamic balance, and functional strength) do not contribute to the onset of musculoskeletal symptoms in school-aged children with GJH, thus preventing inappropriate interventions. Despite the significant decline in physical activity in children with GJH over time, they were not different from their normal mobile counterparts in functional difficulties, physical fitness and quality of life.